مقومات النهضة الإدارية في القرآن الكريم، وتطبيقاتها التربوية على الهيكل الإداري والتنظيمي للتعليم العالي - أبو غوري، عماد محمد; أبو رحمة، محمد حسن خميس (رابطة التربويين الفلسطينيين - قسم الأبحاث والمنشورات, 2024)
هدفت الدراسة للتعرف إلى مقومات النهضة الإدارية في القرآن الكريم، وبيان تطبيقاتها التربوية وخاصة على الهيكل الإداري والتنظيمي للتعليم العالي، واعتمدت الدراسة المنهج الوصفي التحليلي، وتوصلت الدارسة لنتائج منها: تؤكد الدراسة شمول وتكامل مقومات النهضة الإدارية في القرآن الكريم للوظائف والمهارات الإدارية، اهتمام القرآن الكريم بمقومات النهضة الإدارية لإحداث الجودة الشاملة، مراعاة النهضة الإدارية في القرآن الكريم للقيم الإنسانية، والاهتمام بها وبتنميتها، لمقومات النهضة الإدارية في القرآن الكريم تطبيقات على التعليم العالي، ومنها الهيكل الإداري والتنظيمي للتعليم العالي الفلسطيني، وأوصت الدراسة وزارة التعليم العالي الاهتمام بالهيكل الإداري والتنظيمي للتعليم العالي لضمان تحقيق الجودة الإدارية والتقدم بها، وتفعيل التطبيقات التربوية لمقومات النهضة الإدارية على الهيكل الإداري والتنظيمي للتعليم العالي الفلسطيني. The study aimed to identify the components of the administrative renaissance in the Holy Qur’an, and demonstrated its educational applications, especially on the administrative and organizational structure of higher education. The study adopted the descriptive and analytical approach, and the study reached results including: The study confirms the comprehensiveness and integration of the components of the administrative renaissance in the Holy Qur’an for administrative jobs and skills, the interest of the Holy Qur’an. The elements of administrative renaissance to achieve comprehensive quality, taking into account human values, and paying attention to their development, have applications to the administrative and organizational structure of Palestinian higher education. The study recommended that the Ministry of Higher Education pay attention to the administrative and organizational structure of higher education to ensure the achievement of administrative quality, and activate educational applications on the administrative and organizational structure of Palestinian higher education
Keywords: النهضة الإدارية -- الآيات القرآنية -- التطبيقات التربوية -- النظام المؤسسي -- التعليم الجامعي